Kompetensi Memesona Bagi Calon Guru Pendidikan Agama Islam Pada Abad 21 Guna Merangkul Generasi Z - Yusnem, Fetriade; Iltavia, Iltavia; Rahmi, Fathur (SURAU : Journal of Islamic Education, 2023)
Abstract The transformation of the world of education which is rapidly changing with the times requires an educator who has outstanding competencies to be able to embrace generation Z in the 21st century. This research discusses the analysis of teacher competencies that are attractive for the 21st century for prospective educators at UIN Sjech M.Djamil Djambek Bukittinggi. This research aims to measure the competence of teachers in the 21st century as a preparation for educators to teach in schools for the future. The type of research used is qualitative research with descriptive analysis research methods. The data collection technique in this research uses a charming competency test using Google Form. The research subjects were 104 FTIK students of the Islamic Religious Education Study Program at UIN Sjech M.Djamil Djambek Bukittinggi. The results of this research are as follows: the score for the sub-topic of nationalism, authoritative attitude is 37 in the poor category; the score for the sub-topic of patriotism and discipline was 52.9 in the quite good category; the score for the sub-topic appreciates a difference of 58.7 in the quite good category; the score for the sub-topic of prioritizing common interests, maintaining Indonesia's natural wealth and community attitudes was 93.3 in the very good category; the score for the sub-topic of appreciating the cultural riches of other nations was 27.9 in the poor category; the score for the assertive attitude sub-topic was 32.7 in the poor category; the score for the sub-topic attitude of full soul calling was 64.4 in the good category; the score for the wholehearted attitude sub-topic was 67.35 in the good category; The score for the sub-topic of generosity was 57.36 in the quite good category. The conclusion of this research is that the average competence of prospective educators is only 59.08%. If this is left unchecked, it will not only have an impact on educators but will also make it difficult for teachers to accommodate students at school.AbstrakTransformasi dunia pendidikan yang cepat berubah mengikuti zaman memerlukan seorang pendidik yang memiliki kompetensi memesona agar dapat merangkul generasi Z di abad 21. Penelitian ini membahas tentang analisis kompetensi guru yang memesona abad 21 bagi calon pendidik UIN Sjech M.Djamil Djambek Bukittinggi. Penelitian ini bertujuan untuk menganalisa kompetensi guru yang memesona abad 21 sebagai persiapan calon pendidik mengajar di sekolah untuk masa yang akan datang. Jenis penelitian yang dipakai adalah penelitian kualitatif dengan metode peneitian deskriptif analisis. Teknik pengumpulan data dalam penelitian ini menggunakan tes kompetensi memesona menggunakan google form. Subjek penelitian adalah 104 mahasiswa FTIK Program Studi Pendidikan Agama Islam UIN Sjech M.Djamil Djambek Bukittinggi. Hasil penelitian ini adalah sebagai berikut: skor untuk sub topik nasionalisme, sikap berwibawa sebesar 37 pada kategori kurang baik; skor untuk sub topik patriotisme, sikap disiplin sebesar 52,9 pada kategori cukup baik; skor untuk sub topik menghargai perbedaan sebesar 58,7 pada kategori cukup baik; skor untuk sub topik mengutamakan kepentingan bersama, mempertahankan kekayaan alam Indonesia serta sikap samaptaÂ sebesar 93,3 pada kategori sangat baik; skor untuk sub topik mengapresiasi kekayaan budaya bangsa lain sebesar 27,9 pada kategori kurang baik; skor untuk sub topik sikap tegas sebesar 32,7 pada kategori kurang baik; skor untuk sub topik sikap penuh panggilan jiwa sebesar 64,4 pada kategori baik; skor untuk sub topik sikap kesepenuhhatian sebesar 67,35 pada kategori baik; skor untuk sub topik kemurahhatian sebesar 57,36 pada kategori cukup baik. Kesimpulan dari penelitian ini adalah rata-rata kompetensi memesona yang dimiliki calon pendidik hanya sebesar 59,08 %. Apabila hal ini dibiarkan, tidak hanya berdampak kepada pendidik saja tetapi juga berdampak kepada sulitnya guru untuk membersamai siswa di sekolah.